2018
DOI: 10.1055/s-0038-1675786
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Profile of Middle Ear Fluid with Recurrent Acute Otitis Media Infection Using Culture Independent 16S rDNA Gene Sequencing

Abstract: Background Recurrent otitis media is one of the common infections of childhood. The causative bacterial pathogen is one of the major risk factors of recurrent infection. With limited availability of Indian data, we performed this study to identify the bacterial pathogens. Materials and Methods Otitis media cases were diagnosed based on clinical criteria. Thirty-six middle ear fluid (MEF) samples were collected by tympanocentesis and cultured for pathogens. Seventy-eight per cent of the cases had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…Staphylococcus aureus and Escherichia coli at different concentrations which agreed with the findings ofNagaraj et al (2019) andZeeshan a et al (2018). The study demonstrated that earwax has antibacterial property, which plays a role in protection of the external auditory canal against bacteria.The result of the antibacterial activity of the test agent called earwax showed that the earwax had antibacterial effect on both isolates.…”
supporting
confidence: 86%
“…Staphylococcus aureus and Escherichia coli at different concentrations which agreed with the findings ofNagaraj et al (2019) andZeeshan a et al (2018). The study demonstrated that earwax has antibacterial property, which plays a role in protection of the external auditory canal against bacteria.The result of the antibacterial activity of the test agent called earwax showed that the earwax had antibacterial effect on both isolates.…”
supporting
confidence: 86%